Anisotropic distortion in the perceived direction of motion on the arm - Scinob Kuroki (Scientific Reports, 2023)
Abstract Skin covers the entire body, and its thickness and distribution of mechanoreceptors vary markedly across body parts. It has been shown that the brain is not able to fully compensate for such anisotropy, and as a result, the representational space of touch differs depending on which parts the stimulus is applied to. Here, by contrasting the hand and arm, we investigated the difference in perceived motion. Using a large-area braille display, we were able to present precisely controlled touchable motion stimuli with randomizing stimulus trajectories and varying the size. We found a new perceptual illusion in which the motion direction of stimuli perceived on the arm is rotated regionally, or even flipped. In particular, obliquely moving stimuli that move toward the distal radial are perceived as move toward the proximal radial, and stimuli that move toward the proximal ulnar are perceived as move toward the distal ulnar. This illusion was not observed on the palm, regardless of compensation for the stimulus size. Current study adds a clear example of how presenting the same motion stimuli to different body parts results in a different perception, emphasizing that the perceived tactile space is not uniform and needs to be examined in detail.